Resource allocation for real-time and multimedia communications in TDMA-based wireless networks. (27th July 2009) - Jawhar, Imad; Wu, Jie
In order to support multimedia traffic, QoS routing protocols for Mobile Ad Hoc Networks (MANETs) allow finding a path between two nodes which satisfies the application layer's minimum bandwidth requirements. Currently, such protocols exist for TDMA, and CDMA-over-TDMA environments. However, these protocols do not account for race conditions which can become more significant with increased node mobility, network density and higher traffic loads. This paper provides a QoS routing protocol which enables the network to cope with this and other related problems such as parallel reservations. Furthermore, additional optimisations, which significantly enhance network throughput and efficiency are provided.